From fragmented to functional: Improving rehabilitation data in Georgia's health information systems for better decision-making - Nino Kotrikadze; Akaki Zoidze; George Gotsadze (SSM - Health Systems)
Introduction: Integrating rehabilitation data into health information systems (HIS) is critical for effective healthcare decision-making, especially in low- and middle-income countries (LMICs) like Georgia. Despite legal obligations under the Convention on the Rights of Persons with Disabilities (CRPD) and the Georgia Rehabilitation Service Development Strategy (2023–2027), rehabilitation data in Georgia remains fragmented. This study aims to assess the adequacy of the HIS for rehabilitation in Georgia to support the planning, monitoring, and expansion of rehabilitation service developments in the country. Methods: The cross-sectional study design combined a documentary review with qualitative interviews. The documentary review examined legislative/regulatory documents from official bodies. Qualitative data were collected through 24 semi-structured interviews with stakeholders representing six rehabilitation facilities (four providing services under the Universal Health Care Program (UHCP) with government funding and two on a fee-for-service basis) and two policymakers. NVivo 12 was used to analyze interviews through the first deductive (Health Metrics Network framework) followed by an inductive coding approach. Results: Findings reveal that rehabilitation data in Georgia's HIS are inconsistent, lacking standardized definitions or reporting practices. Differences were identified in data collection practices across facilities. The UHCP facilities employ the functional assessment tool but no standardized reporting persist. Multiple recording modules lack standardization, with variations in the volume and type of data reported. Key challenges include the absence of unified coding systems, incomplete data capture, and reliance on unstructured formats, hindering data analysis and integration. Conclusion: Although Georgia has made progress by integrating rehabilitation services into the UHCP, gaps in HIS still limit effective decision-making. Addressing these gaps requires a standardized data collection framework emphasizing programmatic and functional outcomes, patient-centered measures, and the comprehensive use of existing electronic systems. Strengthening HIS via coordinated stakeholder efforts and streamlined data reporting will improve rehabilitation services and serve as a model for other LMICs.